Water-retaining polymers on the early growth and quality of bushy cashew (Anacardium humile A. St. Hill) seedlings - Soares, Antonio Gabriel Ataide; de Oliveira, Ruthanna Isabelle; Venança, Thaynara Mota; Pinheiro, Gabriela de Oliveira; Matos, Alex Pinto; Pereira, Gustavo Alves; Junior, Gabriel Barbosa da Silva (Comunicata Scientiae, 2020)
Bushy cashew (Anacardium humile A. St. Hill) is an endemic plant species to the Brazilian Cerrado, a region characterized by scarce and poorly distributed rainfall. The use of hydrogel, a water-retaining polymer that features massive water storage and promotes its release into the environment throughout time may be an alternative to reduce the frequency irrigation in the production of bushy cashew seedlings. This study aimed to evaluate the quality and early growth of bushy cashew seedlings as a function of hydrogel doses. The experimental design adopted was in five randomized blocks, with five hydrogel doses (0; 1,0; 2,0; 3,0; and 4,0 g L-1 of soil), and each plot consisting of 10 seedlings, totaling 250 plants. A Yellow Latosol with sandy-loam texture was used for seedling production. The growth evaluation was performed through the variables of emergence speed index, germination percentage, height, diameter, root volume, number of leaves, shoot dry mass, root dry mass, and the Dickson quality index. The results revealed a positive influence of the hydrogel on the growth and quality of bushy cashew seedlings, notably at the dose of 4 g L-1 of soil.